HEDONISME DALAM NOVEL KISAH PENCARIAN CINTA SEJATI DIORAMA SEPASANG ALBANNA KARYA ARI NUR - Januarinda Afra; Hasanuddin WS Hasanuddin WS; Hamidin Hamidin (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purpose of this article: (a) to describe of substance characterization novel Kisah Pencarian Cinta Sejati Diorama Sepasang AlBanna? created by Ari Nur, (b) to describe type behavior hedonism in novel Kisah Pencarian Cinta Sejati Diorama Sepasang AlBanna? created by Ari Nur, (c) to describe impact behavior hedonism in novel Kisah Pencarian Cinta Sejati Diorama Sepasang AlBanna? created by Ari Nur. The method of used is descripyion method encode of this observation is novel about “Kisah Pencarian Cinta Sejati Diorama Sepasang AlBanna” created by Ari Nur, published by P.T. Mizan pustaka, Bandung 2008, a number of 216 pages. Editored manuscribe by Ali Muakhir and Salman Iskandar on step of gathered encode used study method of bibliography. Analysis technical committed with literature theory into novel. The result of this observation to express form of characterist, behaviour, hedonism, and impact of hedonism in novel “Kisah Pencarian Cinta Sejati Diorama Sepasang AlBanna” created by Ari Nur.